Uji aktivitas antibakteri ekstrak herbal terhadap bakteri Escherichia coli - Nurina Rahmawati; Edhy Sudjarwo; Eko Widodo (Faculty of Animal Science, Universitas Brawijaya, 2014)
Several herbs have been evaluated as feed additive for chicken, namely tumeric, white tumeric, javanese ginger and black ginger. The purpose of the research was to examine antibacterial activity (inhibition diameter zone and minimum inhibition concentration test) on several herbs extract toward Escherichia coli. In the experiment, there were 6 treatments namely aquadest 100% (A0), antibiotic tetracycline (A1), tumeric extract (A2), white tumeric extract (A3), javanese ginger extract (A4) and black ginger extract (A5) in response to inhibit Escherichia coli. Variables measured were inhibition diameter zone and minimum inhibition concentration test against challenge on Escherichia coli. The experiment was arranged in one way nested ANOVA based on completely randomized design and if there were different effects among variables it would be tested by Duncan’s multiple range test. The result showed that the use of turmeric extract gave highly significant inhibition diameter zone for Escherichia coli (P<0,01), further test indicated that as low as 50% (w/v) concentration of turmeric extract was enable to show as minimum concentration of inhibition against Escherichia coli. The conclusion of this research was among the herbs, selected turmeric extract showed the highest inhibition diameter zone if challance against Escherichia coli with minimum inhibition concentration of 50% (w/v). Keywords : herbs extract, Escherichia coli, inhibition